The Composition of Portunus pelagicus on the Fishing Ground Area of Danasari Waters, Pemalang Regency - Sri Redjeki; Ria Azizah Tri Nuraini; Hadi Endrawati (Jurnal Kelautan Tropis, 2023)
Blue swimming crab (Portunus pelagicus) is one of the most economically valuable marine products in Indonesia. The crabs productivity was generally still dependent on the population in the wild. Danasari Village is one of the main crab producers in Pemalang Regency. The daily fishing crab activities by fisherman direct an impact on decreasing of the natural crabs resources. This study determined the crabs composition in the fishing ground where usually spotted by the Danasari crab fisherman. This research obtained the information of a composition of female and male crabs, carapace width distribution, growth characterized, and the egg-berried female number. This study conducted on May to July 2022. The result in this research was a male crabs were dominated than females. The carapace width was generally amount 92-112 mm, while the growth characteristic of blue swimming crabs was negative allometric. The female crab gonad maturity was dominated by 2nd level gonad maturity, while the egg-berried female crabs were found 21 crabs totaled from 14 spot fishing grounds. Based on the carapace width distribution, there are a lot of blue swimming crab with undersized in shallow-depth fishing sites, while the crab size mostly above 100 mm already found at each spot in this research. The highest egg-berried female percentage was found at spot 7th and 13rd, where the female crabs at 7th spot were bigger carapace than at 13rd spot areas. These results indicated that crab resources in Danasari Waters and surround area were indicated potentially overfished, proven with undersized berried-female crabs. The management efforts will conduct an environmentally friendly fishing gear, regarding the policy of ministry regulating as to keep crab resources sustainable. In addition, scheduling rules for fishing activities can also be tested to be applied.